Peer mentoring for students with learning disabilities: the importance of shared experience on students’ social and emotional development - Williams, Charles J.; Chen, Jacqueline M.; Quirion, Allison; Hoeft, Fumiko (Frontiers in Education, 2024)
Abstract Students with Learning Disabilities (LDs) can experience classroom challenges that may negatively impact their social and emotional development, and these struggles can put them at risk for mental health issues and lower quality of life. Programs designed to support students with LDs need to consider not only academic skills and accommodations, but also the broader well-being of these students. Among interventions that address holistic student development are mentoring programs that utilize peer mentors (older students who also have LDs). The purpose of this article was to review key literature on the potential benefits of peer mentoring for students with LDs. According to reviewed articles, peer mentoring programs have been implemented in both school and university settings. In addition to conferring academic benefits to mentees, participation in these programs is associated with increased emotional well-being, higher self-esteem, and better communication skills among mentees. These programs may also benefit mentors, but these benefits have been understudied. More research is needed to determine the positive benefits of mentoring for mentors and mentees with similar learning characteristics, above and beyond positive benefits of mentorship in general.